Yoga’s potential for promoting healthy eating and physical activity behaviors among young adults: a mixed-methods study - Allison W. Watts (International Journal of Behavioral Nutrition and Physical Activity, 2018)
Abstract Background A regular yoga practice may have benefits for young adult health, however, there is limited evidence available to guide yoga interventions targeting weight-related health. The present study explored the relationship between participation in yoga, healthy eating behaviors and physical activity among young adults. Methods The present mixed-methods study used data collected as part of wave 4 of Project EAT (Eating and Activity in Teens and Young Adults), a population-based cohort study in Minneapolis-St. Paul, Minnesota. Young adults (n = 1820) completed the Project EAT survey and a food frequency questionnaire, and a subset who reported practicing yoga additionally participated in semi-structured interviews (n = 46). Analyses of survey data were used to examine cross-sectional associations between the frequency of yoga practice, dietary behaviors (servings of fruits and vegetables (FV), sugar-sweetened beverages (SSBs) and snack foods and frequency of fast food consumption), and moderate-to-vigorous physical activity (MVPA). Thematic analysis of interview discussions further explored yoga’s perceived influence on eating and activity behaviors among interview participants. Results Regular yoga practice was associated with more servings of FV, fewer servings of SSBs and snack foods, less frequent fast food consumption, and more hours of MVPA. Interviews revealed that yoga supported healthy eating through motivation to eat healthfully, greater mindfulness, management of emotional eating, more healthy food cravings, and the influence of the yoga community. Yoga supported physical activity through activity as part of yoga practice, motivation to do other forms of activity, increased capacity to be active, and by complementing an active lifestyle. Conclusions Young adult yoga practitioners reported healthier eating behaviors and higher levels of physical activity than non-practitioners. Yoga should be investigated as an intervention for young adult health promotion and healthy weight management.